2010
DOI: 10.1007/s00339-010-5843-5
|View full text |Cite
|
Sign up to set email alerts
|

Process mapping of laser surface modification of AISI 316L stainless steel for biomedical applications

Abstract: A 1.5-kW CO 2 laser in pulsed mode at 3 kHz was used to investigate the effects of varied laser process parameters and resulting morphology of AISI 316L stainless steel. Irradiance and residence time were varied between 7.9 to 23.6 MW/cm 2 and 50 to 167 µs respectively. A strong correlation between irradiance, residence time, depth of processing and roughness of processed steel was established. The high depth of altered microstructure and increased roughness were linked to higher levels of both irradiance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…From the previous studies, it was established that energy densities greater than 6700J/cm 2 resulted in ablation regardless of the residence time [13]. At this energy level sample sparking was observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the previous studies, it was established that energy densities greater than 6700J/cm 2 resulted in ablation regardless of the residence time [13]. At this energy level sample sparking was observed.…”
Section: Discussionmentioning
confidence: 99%
“…This present work focused on samples treated at the high irradiance and low residence time; specifically, samples treated at fluences of 950 and 2096J/cm 2 with each sample repeated three times. A detailed study of the effects of processing parameters on melt pool depth and surface roughness is presented elsewhere [13].…”
Section: Methodsmentioning
confidence: 99%
“…Marrocco et al (2011) proved that post-deposition laser treatment on titanium coating eliminates the residual micro-porosity and forms a high quality corrosion barrier layer [3]. Other authors studied the laser treatments in order to improve the superficial properties of both coatings and bulk materials [9][10][11]. The authors' previous work showed the optimal process parameters of the laser treatment to obtain a compact titanium dioxide layer on cold-sprayed titanium coating [12].…”
Section: Introductionmentioning
confidence: 99%
“…The effects of various laser process parameters and associated morphologies of AISI 316L stainless steel have been investigated. The experiment results showed that a combination of low level of irradiance and long time of residence was the best for lower roughness and moderate depth of processing [12]. Although process parameters are usually optimized to improve the surface morphology, in some cases the process parameters not only influence the surface morphology, but also affect other properties of the surface such as wear and corrosion resistance, therefore, these parameters cannot be reasonably optimized in terms of surface morphology solely.…”
Section: Introductionmentioning
confidence: 97%